Addressing immediate public health needs as part of Afghan evacuees' resettlement to the United States during the COVID-19 pandemic. (April 2023) - Bednar, H.; Powell, R.; Sidibe, T.
Abstract: Objectives: Since the removal of US troops from Afghanistan in 2021, the United States welcomed Afghan evacuees through Operation Allies Welcome. Using cell phone accessibility, the CDC Foundation worked with public-private partners to protect evacuees from the spread of COVID-19 and provide accessibility to resources. Study design: This was a mixed methods study. Methods: The CDC Foundation activated its Emergency Response Fund to accelerate public health components of Operation Allies Welcome, including testing, vaccination, and COVID-19 mitigation and prevention. The CDC Foundation began the provision of cell phones to evacuees to ensure access to public health and resettlement resources. Results: The provision of cell phones provided connections between individuals and access to public health resources. Cell phones provided means to supplement in-person health education sessions, capture and store medical records, maintain official resettlement documents, and assist in registration for state-administered benefits. Conclusions: Phones provided necessary connectivity to friends and family for displaced Afghan evacuees and higher accessibility to public health and resettlement resources. As many evacuees did not have access to US-based phone services upon entry, provision of cell phones and plans for a fixed amount of service time provided a helpful start in resettlement while also being a mechanism to easily share resources. Such connectivity solutions helped to minimize disparities among Afghan evacuees seeking asylum in the United States. Provision of cell phones by public health or governmental agencies can help to provide equitable resources to evacuees entering the United States for social connection, healthcare resources, and resources to assist in the process of resettlement. Further research is needed to understand the generalizability of these findings to other displaced populations.